JENIS DAN KERAPATAN PADANG LAMUN DI PANTAI SANUR BALI - Arthana, I Wayan (Bumi Lestari; Vol 5 No 2)
A Study of kind and density of seagrass bed at Sanur Beach Bali has done. Themethod used quadrate transect of 1x1 m. There were 4 stasiuns observed with 9quadrate transects each.Seagrass species found were seven which belong to two families and four genus,namely Enhalus acoroides, Cymodocea rotundata, Cymodocea serrulata, Halophilaovalis, Halodule uninervis, Halodule pinifolia and Syringodium isoetifolium. Thedistribution of seagrass density was more in the middle of the lagoon which is deeper andlower temperature variation. The density of seagrass bed varied of 40 - 338individuals/0,55 m2 and dominated by Enhalus acoroides. The density reduce to thelocation that more fishing activities, landing boats and disturbance by tourists.
Keywords: seagrass, coastal ecosystem, lagoon